Non-endometrioid endometrial cancer: Analysis of different adjuvant treatment modalities - Gonçalo Nogueira-Costa; Inês Eiriz; Sofia Braga (Cancer Treatment and Research Communications, 2022)
Background: Adjuvant treatment for endometrial carcinoma (EC) is decided based on risk assessment. Tumors of non-endometrioid (NE) histology are classified as high-risk and adjuvant treatment is recommended. Materials and Methods: We analyzed retrospectively all NEEC patients treated in two Portuguese oncology centers, between 2009 and 2018. Comparison of adjuvant modalities were performed by overall survival (OS) and disease-free survival (DFS) analysis. Results: A total of 66 patients were included, with mean age 69 years. Serous histology was found in 34 patients (51.5%), clear-cell in 13 (19.7%) and carcinosarcoma in 18 (27.3%). Based on FIGO staging-system, 34 (51.5%) patients were diagnosed at stages III-IV. Following surgery, no further treatment was performed in 16 patients (24.4%), 11 (16.7%) received isolated chemotherapy (CT), 11 (16.7%) isolated radiotherapy (RT) and 28 (42.4%) combination therapy (CT+RT). Kaplan-Meier analysis showed higher median (m)DFS in the CT+RT group: 30.7 months (m) compared to RT alone: 14.1 m. The mDFS of the isolated CT group was 10.8 m and for patients with no further treatment it was 5.7 m, p = 0.03. Median OS was also increased in the combination group CT+RT (78.3 m) compared to isolated RT (64.3 m), isolated CT (37.3 m) and no further treatment (46.7 m), p=0.005. Multivariate Cox-regression using CT+RT as reference, showed hazard-ratio of 3.5 (p = 0.05) and 4.5 (p = 0.01) for the CT and for no-treatment group respectively. Conclusions: In NEEC patients, DFS and OS analysis showed better prognosis in combination of CT+RT. Patients that underwent only RT had better survival outcomes when compared to those treated with CT only.